x + y . x + y - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Talks with schoolchildren about their relations with and attitudes towards their parents; reading of love poetry; the problem of homeless people in Russia. Series description: Educational and entertaining program for children and young people. Беседа со школьниками об их взаимоотношениях и отношениях к родителям, идеалах; чтение стихов о любви; проблема бездомных в России. Описание серии: Образовательно-развлекательная программа для детей и молодежи